2022
DOI: 10.3847/2041-8213/aca025
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Kilonovae: Long-lasting Electromagnetic Counterparts to Binary Mergers in the Accretion Disks of Active Galactic Nuclei

Abstract: We investigate the dynamics and electromagnetic (EM) signatures of neutron star–neutron star (NS–NS) or neutron star–black hole (NS–BH) merger ejecta that occur in the accretion disk of an active galactic nucleus (AGN). We find that the interaction between ejecta and disk gas leads to important effects on the dynamics and radiation. We show five stages of the ejecta dynamics: gravitational slowing down, coasting, Sedov–Taylor deceleration in the disk, reacceleration after the breakout from the disk surface, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…On the other hand, as the cavity is much more tenuous than the AGN disk but still denser than the interstellar medium, these jet, ejecta, and outflow are not significantly decelerated but still interact with the cavity medium (e.g., Yuan et al 2022), and the produced EM emissions propagate within the cavity environment as well (e.g., Kimura et al 2021b), which may thus lead to characteristic signals differing from the ones in an unperturbed AGN disk or in a classical interstellar medium. Also, as the underdense cavity has a limited size, matter penetrating along the AGN disk will first collide with the cavity and then AGN disk gas, causing a later effective loss of the kinetic energy and thereby later brightening, which may apply to the events with wide-angle ejecta and outflow, as a star tidally disrupted by a stellar-mass BH (e.g., Perets et al 2016;Yang et al 2022), or BH-NS and NS-NS mergers (e.g., Zhu et al 2021a;Ren et al 2022). A more precise description of the cavity structure and the properties of various EM events occurring in the cavity-AGN disk environment are left for follow-up work.…”
Section: Potential Role Of Outflow Cavity Surrounding Comentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as the cavity is much more tenuous than the AGN disk but still denser than the interstellar medium, these jet, ejecta, and outflow are not significantly decelerated but still interact with the cavity medium (e.g., Yuan et al 2022), and the produced EM emissions propagate within the cavity environment as well (e.g., Kimura et al 2021b), which may thus lead to characteristic signals differing from the ones in an unperturbed AGN disk or in a classical interstellar medium. Also, as the underdense cavity has a limited size, matter penetrating along the AGN disk will first collide with the cavity and then AGN disk gas, causing a later effective loss of the kinetic energy and thereby later brightening, which may apply to the events with wide-angle ejecta and outflow, as a star tidally disrupted by a stellar-mass BH (e.g., Perets et al 2016;Yang et al 2022), or BH-NS and NS-NS mergers (e.g., Zhu et al 2021a;Ren et al 2022). A more precise description of the cavity structure and the properties of various EM events occurring in the cavity-AGN disk environment are left for follow-up work.…”
Section: Potential Role Of Outflow Cavity Surrounding Comentioning
confidence: 99%
“…The AGN disk channel can contribute to a large amount of unique BH-BH, BH-NS, and NS-NS mergers (e.g., Tagawa et al 2020a;McKernan et al 2020bMcKernan et al , 2020aTagawa et al 2021;Samsing et al 2022) and extreme mass ratio inspirals (e.g., Pan & Yang 2021a;Pan et al 2022) events for gravitational wave (GW) observations. EM events, such as gamma-ray bursts and kilonovae (Perna et al 2021a;Zhu et al 2021a;Ren et al 2022;Wang et al 2022;Yuan et al 2022), supernovae (Zhu et al 2021b;Grishin et al 2021;Moranchel-Basurto et al 2021), accretion-induced collapses of NSs (Perna et al 2021b) and white dwarfs (Zhu et al 2021b), and microtidal disruption events (Yang et al 2022), occurring in the AGN disk show characteristic transient features. All the GW and EM transients are distinguishable from the same events taking place in the classical interstellar medium on account of the COs lying within the extremely dense environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few potential AGN disk transients were detected although their origins were still unclear (Hinkle et al 2022;Holoien et al 2022), and more AGN disk transients might be recorded in previous optical survey projects. Lightcurves of AGN disk transients could have similar peak brightness, peak time, and evolution pattern with those of TDEs (Zhu et al 2021d;Grishin et al 2021;Ren et al 2022) so that some AGN disk transients could be wrongly identified as TDEs. Future theoretical studies and observations may extend our understanding and help to give a better estimation of the contribution to the neutrino background by AGN disk transients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the surrounding dense atmosphere may lead to unique observable electromagnetic (EM)signatures of these transients in AGN disks. SN and kilonova emissions in AGN disks could be outshone by the AGN disk emissions (Zhu et al 2021d, while shock breakout signals and interaction emissions between ejecta and disk atmosphere can be bright enough to be detected (Zhu et al 2021d;Grishin et al 2021;Ren et al 2022). The EM signals of AGN GRBs are highly diverse, being dependent on the burst properties, the disk structure, and the location of bursts (Cheng & Wang 1999;Perna et al 2021a;Zhu et al 2021e;Kimura et al 2021;Lazzati et al 2022;Ray et al 2022;Wang et al 2022;Yuan et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Lazzati et al (2023) proposed that GRB 191019A originated in a binary compact merger with an intrinsic prompt emission duration of ∼1.1 s, which is stretched in time by the interaction with a high-density external medium ∼10 7 -10 8 cm −3 (Lazzati et al 2022). If this is the case, a kilonova emission associated with GRB 191019A should be powered after the merger of the compact stars, and the contribution of an ejecta-circumstellar medium (CSM) interaction producing a kilonova cannot be ignored in such a dense external medium (Qi et al 2022;Ren et al 2022). In previous studies, the ejecta-CSM interaction has been invoked to interpret the observations of some superluminous supernovae (Chevalier & Fransson 1994;Smith & McCray 2007;Chevalier & Irwin 2011;Chatzopoulos et al 2012Chatzopoulos et al , 2013Nicholl et al 2014;Wang et al 2016;Liu et al 2018), but has never been used to interpret any kilonova emission associated with short GRBs.…”
Section: Introductionmentioning
confidence: 99%